2021
DOI: 10.1093/cid/ciab774
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity Modifies the Risk of Long-term Neurodevelopmental Impairments After Invasive Group B Streptococcus Infections During Infancy in Denmark and the Netherlands

Abstract: Background Preterm birth and neonatal infections are both associated with mortality and long-term neurodevelopmental impairments (NDI). We examined whether the effect of invasive group B streptococcus disease (iGBS) on mortality and long-term NDI differs for preterm and term infants, and whether co-occurrence of iGBS and prematurity leads to worse outcome. Methods Two nationwide cohort studies of children with a history of iG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The clinical characteristics of early GBS infection, namely age at disease onset and meningitis versus sepsis, are broadly the same as described in other studies from high‐income countries 1,3 . Our finding that preterm birth 3,25 and multiple gestation 23 was associated with LOD/VLOD has also been reported. In line with previous studies, we found that nearly 50% of infants with LOD/VLOD were born preterm, 15,26 confirming that infants born preterm are susceptible to invasive GBS infection throughout the first year of life.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The clinical characteristics of early GBS infection, namely age at disease onset and meningitis versus sepsis, are broadly the same as described in other studies from high‐income countries 1,3 . Our finding that preterm birth 3,25 and multiple gestation 23 was associated with LOD/VLOD has also been reported. In line with previous studies, we found that nearly 50% of infants with LOD/VLOD were born preterm, 15,26 confirming that infants born preterm are susceptible to invasive GBS infection throughout the first year of life.…”
Section: Discussionsupporting
confidence: 86%
“…[35][36][37][38][39] Moreover, it is well established that GBS infection and preterm birth independently increase the risk of mortality and NDDs. 25,40 A recent study found that the combined effects of GBS infection and preterm birth lead to a worse outcome than would be expected on the basis of their individual effects. 25 Partly consistent with this, we found that infants born preterm with GBS had a higher CFR and were twice as likely as term-born infants with GBS to develop any NDD.…”
Section: Eodmentioning
confidence: 99%
“…Prematurity, low birth weight, maternal colonisation and multiple-gestation pregnancies are all risk factors for invasive GBS 8 9. GBS meningitis is associated with significant neurodevelopmental impairment10 and preterm infants are both at greater risk of developing invasive GBS and also at greater risk of consequent neurodevelopmental impairment 11…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity increases the risk of invasive disease, case fatality and recurrence1 8 and increases the risk of neurodevelopmental impairment associated with GBS infection 11. In addition to the iatrogenic risks of prolonged hospital admission, indwelling devices and gut dysbiosis from antibiotic use, the neonatal immune system is immature, causing susceptibility to infection and impacting both innate and adaptive arms of immunity 15.…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark and the Netherlands, any history of invasive GBS was associated with greater rates of neurodevelopmental injury versus unexposed newborns, as well as a higher risk of moderate and severe disability requiring educational support ( Horváth-Puhó et al, 2021 ). Moreover, preterm infants were at the highest risk of NDI ( Horváth-Puhó et al, 2022 ). A cohort study of GBS meningitis survivors in the United States assessed children younger than 6 years using the Mullen Scales of Early Learning to assess language, motor and cognitive ability.…”
Section: Clinical Outcomes and Risk Factors Associated With Early-ons...mentioning
confidence: 99%